SAT0052 TNFγ adherent BM-DC efficiently inhibit collagen-induced- arthritis, and delayed skin graft rejection in mouse. (23rd January 2014) - Brikci-Nigassa, L.; Touraine, J.-L.; Miossec, P.; Eljaafari, A.
Abstract : Background: Rheumatoid Arthritis (RA) is a chronic inflammatory disease, initiated by a break in self-tolerance. Tolerogenic dendritic cells (Tol-DC) are involved in the maintenance of tolerance to antigen, but are deficient in RA. Objectives: Our ultimate objective is to use Tol-DC for the treatment of patients with severe refractory RA. Therefore, in this project, we aimed to validate this approach by evaluating the therapeutic action of Tol-DCs in a type II collagen-induced arthritis murine model Methods: We have previously reported that DC mediated by IFNg plus GM-IL4 are tolerogenic in human (1). Herein, mouse Tol-DC were prepared by using this protocol, except that bone-marrow mononuclear cells were used instead of blood monocytes. Arthritis was induced with 100 μg of type II collagen in 8–10-week-old DBA/1 mice, following two steps of sensitization and induction. Allogenic skin transplantation was performed by using Balb/c mice, which received skin graft from DBA/1 mice, after sublethal irradiation Results: In contrast to human, IFNγ-treated DC did not resist to maturation in mouse, but died, probably by exhaustion. Moreover, treatment of bone marrow cells with GM-IL4 resulted in the appearance of adherent DC in mouse, but not in human Maturation of mouse adherent-DC with TNFa induced them to exert tolerogenic properties, in-vitro . In vivo, those cells inhibited collagen induced arthritis (p<0.01, at D57, and D65), following their intra-peritoneal injection at the concentration of 2×10 5, at the time of induction with collagen. Such induction of tolerance was confirmed in a skin graft mouse model, where rejection was delayed from day 8.5 to day 14.7, following only one injection of TNFa-adherent DC. Conclusions: We demonstrate herein that TNFa-adherent DC are endowed with efficient tolerogenic properties in mouse, but point out major differences between mouse and human in the generation of Tol-DC. Indeed, GM-IL4 induced the appearance of adherent BM-DCs in mouse but not in human, whereas IFNg induced Tol-DC in human, but not in mouse. These results underline thus the difficulties to predict the beneficial effects of such cell therapies in human, by using rodent studies. References: Assia Eljaafari; Yin-Ping Li; Pierre Miossec. J.Immunol: 2009;183:2932-45. Disclosure of Interest: None Declared